Pengaruh Bauran Pemasaran Dan Kualitas Layanan Terhadap Kepuasan Konsumen J.CO Donuts Dan Coffee Artos Magelang - Farikha Nurlaela; Yacobo P. Sijabat (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
The Magelang branch of J.CO Donuts & Coffee is the market leader for the donut and coffee business in Magelang City. However, nowadays there are many brand competitors offering donuts and coffee similar to J.CO Donuts & Coffee. These competitors are both from multinational brands, based on observations via Google Maps it is known that there are 206 brands in Magelang in the form of cafes and donut businesses. because many competitors make consumers have many other choices and increase the possibility of customers choosing to enjoy coffee other than J.CO Donuts & Coffee. The research design used in this research is descriptive statistical research using a quantitative approach. In this study, the sample was taken using random sampling technique, the sample size in this study was determined by the Cochran formula, the calculation was rounded off to 96 samples. The data analysis technique used by the researcher is multiple linear regression analysis. The correlation coefficient value of 0.29 in the marketing mix means that any increase in the marketing mix will increase consumer satisfaction by 0.29 or 29%. The correlation coefficient value of 0.78 means that any increase in service quality will result in customer satisfaction of 0.78 or 78%. This means that the higher the work environment, the performance of teachers and employees will increase. This study concludes that the marketing mix and service quality affect customer satisfaction at J.CO Donuts & Coffee, Artos Mall Magelang branch..